ANALISIS TERHADAP PERMASALAHAN HUKUM PENGUASAAN TANAH DENGAN HAK GUNA USAHA DI KALIMANTAN (STUDI PUTUSAN: PUTUSAN MAHKAMAH AGUNG NOMOR 121 K/TUN/2017) - Nadhil Rifqi Izhhar; Hasni Hasni (Fakultas Hukum Universitas Tarumanagara, 2019)
The law of the land Indonesia in the act of no. 5 1960 basic provisions concerning this agrarian law based on article 33 paragraph 3 constitution of the Republic of Indonesia 1945. In long-term development the role of land to meet various purposes will increase, good as a live and for business activities. The high level of demand will ground , present us on various problems quaint and still unsolved in an unsatisfactory manner for all parties. Usage rights business have had the use as agricultural land, fisheries, or farmers usage rights a business are also was in directly controlled by the state with a term 25 years or 35 years old and if necessary it could be prolonged 25 years, the broad at least usage rights business at least 5 acres. The various kinds of problems land around land and land together have a Cultivation Rights Title itself such a delicate and complicated it feels conflict land that is just keep on coming from the opening of the land and forest , damage to the customary overlapping permission and many other conflict certain harming other parties. The results of the investigations and analysis Forest Watch Indonesia has indicated the occurrence of violations of related to the licensing of some companies by the district government Long Bentuq area. Forest watch indonesia found the existence of overlapping permission between companies the oil palm with a company from various sectors which are all active operating in the same location but it happened to the forest customary, eviction cemetery land and sengon and cocoa plantations belonging to society is in the village Long Bentuq. The approach used by the writer among others is the approach comparative and law.